Low-Dose Ammonium Preconditioning Enhances Endurance in Submaximal Physical Exercises - Igor Mindukshev; Julia Sudnitsyna; Nikolay V. Goncharov; Elisaveta Skverchinskaya; Irina Dobrylko; Elena Nikitina; Alexandr I. Krivchenko; Stepan Gambaryan (MDPI AG, 2021)
Preconditioning is often used in medicine to protect organs from ischemic damage and in athletes to enhance the performances. We tested whether low-dose ammonium preconditioning (AMP) could have a beneficial effect on physical exercises (PE). We used Cardiopulmonary Exercise Testing (CPET) on a treadmill to investigate the effects of low-dose AMP on the physical exercise capacity of professional track and field athletes and tested twenty-five athletes. Because of the individual differences between athletes, we performed a preliminary treadmill test (Pre-test) and, according to the results, the athletes were randomly allocated into the AMP and control (placebo, PL) group based on the similarity of the total distance covered on a treadmill. In the AMP group, the covered distance increased (11.3 ± 3.6%, p < 0.02) compared to Pre-test. Similarly, AMP significantly increased O2 uptake volume-VO2 (4.6 ± 2.3%, p < 0.03) and pulmonary CO2 output-VCO2 (8.7 ± 2.8%, p < 0.01). Further, the basic blood parameters (pH, pO2, and lactate) shift was lower despite the greater physical exercise progress in the AMP group compared to Pre-test, whereas in the placebo group there were no differences between Pre-test and Load-test. Importantly, the AMP significantly increased red blood cell count (6.8 ± 2.0%, p < 0.01) and hemoglobin concentration (5.3 ± 1.9%, p < 0.01), which might explain the beneficial effects in physical exercise progress. For the first time, we showed that low-dose AMP had clear beneficial effects on submaximal PE.